2021
DOI: 10.1371/journal.pgen.1009318
|View full text |Cite
|
Sign up to set email alerts
|

Ush regulates hemocyte-specific gene expression, fatty acid metabolism and cell cycle progression and cooperates with dNuRD to orchestrate hematopoiesis

Abstract: The generation of lineage-specific gene expression programmes that alter proliferation capacity, metabolic profile and cell type-specific functions during differentiation from multipotent stem cells to specialised cell types is crucial for development. During differentiation gene expression programmes are dynamically modulated by a complex interplay between sequence-specific transcription factors, associated cofactors and epigenetic regulators. Here, we study U-shaped (Ush), a multi-zinc finger protein that ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…All 5 members of the GATA family of transcription factors are predicted to regulate the expression of DEGs in noni and L-DOPA treatment, along with srp being predicted to also regulate DEG expression in HA treatment, but only GATAd is significantly upregulated in L-DOPA treatment. U-shaped, the Friend of GATA protein that binds GATA family of transcription factors that has been previously shown to be involved in fatty acid metabolism (Lenz et al 2021) is significantly upregulated in L-DOPA treatment. Expression of GATA factors may be responding to noni and L-DOPA treatment in order to help metabolize volatile fatty acids found in noni fruit that are concurrently experienced by D. sechellia in their natural environment when feeding on noni fruit.…”
Section: Discussionmentioning
confidence: 99%
“…All 5 members of the GATA family of transcription factors are predicted to regulate the expression of DEGs in noni and L-DOPA treatment, along with srp being predicted to also regulate DEG expression in HA treatment, but only GATAd is significantly upregulated in L-DOPA treatment. U-shaped, the Friend of GATA protein that binds GATA family of transcription factors that has been previously shown to be involved in fatty acid metabolism (Lenz et al 2021) is significantly upregulated in L-DOPA treatment. Expression of GATA factors may be responding to noni and L-DOPA treatment in order to help metabolize volatile fatty acids found in noni fruit that are concurrently experienced by D. sechellia in their natural environment when feeding on noni fruit.…”
Section: Discussionmentioning
confidence: 99%
“…iCLIP2: Individual nucleotide-resolution UV-crosslinking and immunoprecipitation 2 was performed as described in (Buchbender et al, 2020). Briefly, S2 cells expressing GFP-tagged dMi-2 (Lenz et al, 2021) and untagged S2 cells were washed with cold 1× PBS. Protein-RNA cross-linking was performed at 254 nm UV light (300 mJ/cm 2 ) using a Stratagene Stratalinker.…”
Section: Methodsmentioning
confidence: 99%
“…We asked if the propensity of dMi-2 to crosslink to a given mRNA was a function of the expression level of that mRNA. We plotted the number of iCLIP2 crosslinks to a given mRNA against the expression level of that mRNA as determined by RNA-seq (Lenz et al, 2021) (Figure 1C, see Methods for details). This demonstrated that there was no strict linear correlation between RNA expression level and the number of dMi-2 iCLIP2 crosslinks.…”
Section: Dmi-2 Associates With Thousands Of Mrnas In Vivomentioning
confidence: 99%
See 2 more Smart Citations